Royal journeys in early modern Europe
1 online resource (x, 248 pages)
Keywords: "Authored by a unique combination of university academics and heritage professionals this book offers new perspectives on journeys made by Henry VIII and other monarchs, their political and social impact and the logistics required in undertaking such trips. It explores the performance of kingship and queenship by itinerant monarchs, investigating how, by a variety of means, they engaged and interacted with their subjects, and the practical and symbolic functions associated with these activities. Moving beyond the purely English experience, it provides a European dimension by comparing progresses in England and France. Royal marriage and the royal progress share common features which are considered through an analysis of the trans-European journeys made by future spouses, notably Anne of Cleves. The book also reveals the significance of the art and architecture of houses and palaces, and how the celebrated meeting of English and French kings at the Field of Cloth of Gold in 1520 was part of a wider diplomatic performance full of symbolism including the exchange of gifts and socialising between the two royal courts. Drawing on contemporary art, material culture and surviving buildings it will be of interest to all who enjoy the intrigue and splendour of sixteenth century courts"--